Influences of Classical Indian Music in Albert Roussel’s Evocations - Karácsony, Noémi; Rucsanda, Mădălina Dana (Babes-Bolyai University Cluj-Napoca, 2021)
An important figure of early 20th century music, the French composer Albert Roussel was deeply influenced by his encounter with India, which led to the composition of several orientalist works. The present paper aims to disclose the influences of classical Indian music in the orchestral work Evocations. Despite the Impressionist sound of the musical discourse, a careful analysis reveals the incorporation of several scalar structures in which Hindu rāgas can be recognized. Roussel goes beyond the musical representation of India: his goal is not the creation of a musical work with powerful oriental sound, but the evocation of the impact this encounter had on his creation. Situated at the crossroad of several stylistic orientations, Roussel incorporates Impressionist, Neo-classical and Post-romantic influences in rigorously devised structures, aiming to create an unusual and novel sound.
Keywords: Albert Roussel; orientalism; Impressionism; India; rāga